Halide abstraction as a route to cationic transition-metal complexes containing two-coordinate gallium and indium ligand systems - Bunn, N; Aldridge, S; Kays, D; Coombs, N; Rossin, A; Willock, D; Day, J; Jones, C; Ooi, L (2005)
Halide abstraction chemistry offers a viable synthetic route to the cationic two-coordinate complexes [{Cp*Fe(CO)2} 2(μ-E)]+ (7, E = Ga; 8, E = In) featuring linear bridging gallium or indium atoms. Structural, spectroscopic, and computational studies undertaken on 7 are consistent with appreciable Fe-Ga π-bonding character; in contrast, the indium-bridged complex 8 is shown to feature a much smaller π component to the metal-ligand interaction. Analogous reactions utilizing the supermesityl-substituted gallyl or indyl precursors of the type (η5-C5R5)Fe(CO)2E(Mes*)X, on the other hand, lead to the synthesis of halide-bridged species of the type [{(η5-C5R5)Fe(CO)2E(Mes*)} 2(μ-X)]+, presumably by trapping of the highly electrophilic putative cationic diyl complex [(η5-C 5R5)Fe(CO)2E(Mes*)]+. © 2005 American Chemical Society.